1999
DOI: 10.1002/(sici)1097-4660(199909)74:9<852::aid-jctb131>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic molecular modelling - the computational chemistry of metallocenes: a review

Abstract: The application of ab initio, density functional theory and molecular mechanical methods to the modelling of metallocenes, particularly ferrocene, is reviewed. Approaches to the representation of the metal-ring p-bonding in molecular mechanics and the quality of computed results from ab initio and density functional theory serve to illustrate the utility of modelling studies in organometallic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…The main interactions which stabilize the titanocene / cyclodextrin complex in vacuum were bond stretching energy, the angle bending energy, the torsional energy, and the energy arising from van der Waals interactions of non-bonded pairs of atoms. Due to the fact that all titanocene compounds from the studied series are chemically similar molecules, we have an internal consistency from the force field point of view [15,40-49]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main interactions which stabilize the titanocene / cyclodextrin complex in vacuum were bond stretching energy, the angle bending energy, the torsional energy, and the energy arising from van der Waals interactions of non-bonded pairs of atoms. Due to the fact that all titanocene compounds from the studied series are chemically similar molecules, we have an internal consistency from the force field point of view [15,40-49]. …”
Section: Resultsmentioning
confidence: 99%
“…These problems could be resolved in two ways: synthetically modifying the titanocene structure (laborious, other physico-chemical and biological analyses needed) or finding new formulations with enhanced properties [11,13,15,19,24-27]. Natural or chemically modified cyclodextrins (cyclic oligosaccharides with hydrophobic inner cavities and hydrosolubilizing outer groups) are widely used for protection, enhancing water solubility, and controlled release properties of bioactive compounds [28-34].…”
Section: Introductionmentioning
confidence: 99%
“…A review [26] of the computational chemistry of metallocenes investigated the application of ab initio and DFT methods to the modelling of transition-metal complexes and in particular ferrocene. It concluded that, in general, DFT methods could reproduce geometries for transition-metal complexes much more accurately than MP2 calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The success of the refinement, for which R G = 0.059 (R D = 0.043), can be gauged on the basis of the radialdistribution and experimental -theoretical difference \P-C ring -P 120.3(4) 120.5 -p 26 \C ring -P-P 99.6(2) 99.3 -a Refers to B3PW91/aug-cc-pVQZ-PP/6-311+G*. b Distances (r) are in pm, angles (\) and torsional angles (/) in°.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclopentadiene (Cp) is the most commonly used reagent for the synthesis of many metallocenes which contains transition metals and their derivatives on the account of the wide range of their applications [14][15][16] and it is one of the versatile ligands in organometallic chemistry [17]. Since the discovery of ferrocene [18,19], the Cp chemistry of the main-group elements (s-and p-block elements) has experienced great progress, especially for last two decades [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%